The Effect of Green Intrinsic and Extrinsic Motivation on Green Product Purchase Behavior Mediated by Green Product Purchase Intention (Jurnal Manajemen Bisnis, 2025)
This study analyzes the influence of intrinsic and extrinsic motivation on purchase intention and purchase behavior of green products, with purchase intention as the mediator variable. The purpose of this study is to understand how internal (environmental concerns) and external factors (social influences, incentives) influence consumers' decisions in purchasing green products. A quantitative approach was used, with data collected through an online survey of 200 respondents. The data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study show that both intrinsic and extrinsic motivation have a significant effect on the purchase intention and purchase behavior of green products. Intrinsic motivation, which is driven by personal values related to environmental sustainability, has a greater influence on purchase intention than extrinsic motivation. However, external factors such as discounts and social influences also play an important role in purchasing decisions. Purchase intent serves as a powerful mediator, which means that the higher the purchase intent, the more likely the consumer is to make a purchase. These findings suggest that companies incorporate intrinsic and extrinsic motivations in their marketing strategies to promote green products and support environmental sustainability.